Perancangan Beban Komplemen pada PLTMH 1000 Watt - Syahir Mahmud; Limbran Sampebatu (Widya Teknik, 2020)
The use of erratic loads will result in frequency changes and make electrical equipment (loads) easily damaged. Changes in load according to the demands of consumer loads often occur in small-scale MHP. So this study analyzes the shape and configuration of the complement load that is suitable for use on a 1000 Watt MHP to maintain a constant rotation of the MHP engine. This study analyzes the amount of change in the metal plate surface needed to get a load of one hundred watts. The type of metal plate as the object of this research is one milli meter steinless steel plate which is made in the form of a rectangular geometric. The metal plates are arranged in parallel with each other and given an electric voltage and then dipped in water gradually while measuring the amount of current flowing in the experimental circuit. The water used is PAM water and enriched with table salt to reach 0.05% gram / ml salinity. This large current is converted into power that flows into water. The results of this measurement are analyzed in simple statistics to get the power value (Watt) of the broad union of stainless steel plates. The results show that the design of the complement load can be practically used to overcome changes in the 1000 Watt PLTM load with a load sensitivity of 0.45A equivalent to the electrode surface area of 362 mm2. The range of the ability to complement the load of this design results from 80% to 2% of the 1000 Watt PLTMH load. And it is not recommended to use a single pole electrode (single pole) because it will potentially cause electrical hazards around the 1000Watt PLTMH installation site.